Indonesian Happiness Factor: A Panel Data Analysis - Rakhmawati Rakhmawati (Universitas Negeri Malang, 2024)
The measurement of welfare level is one of the success benchmarks of a country's developmental program. Welfare assessments in the form of subjective well-being (SWB) can complement the objective measures. In assessing SWB, economists use happiness and life satisfaction questions. Therefore, this study aims to analyze the factors that influence individual happiness in Indonesia. The panel data from the last two waves of the Indonesia Family Life Survey (IFLS), namely IFLS 4 (2007) and IFLS 5 (2014) were used. The analytical tool was panel data regression with a fixed effect approach. The results showed religiosity, generalized trust, altruism, and education-age interaction significantly affected happiness levels. This study implies the higher the year of education, the more positive the effect of age on happiness level. Furthermore, the control variables, namely marital status, subjective health, perceived safety, and per capita expenditure are significant, while unemployment affected the happiness level of only the male sample. The government and public figures in Indonesia may promote initiatives that facilitate religiosity, trust, and altruism development, for instance, promoting activities that require involvement from different stakeholders in the community. They also should become role models showing altruism and religiosity.